A calorimetric system for charge and kinetic energy characterizations of pulsed electron beams; Radiation Measurements; Vol. 143 - Serebrennikov M. A. Maksim Anatolevich; Adamov E. V. Egor Vladimirovich; Poloskov A. V. Artem Viktorovich; Yu Xiao; Egorov I. S. Ivan Sergeevich (2021, 2021)
Title screen